2021
DOI: 10.1101/2021.04.06.438723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepDDS: deep graph neural network with attention mechanism to predict synergistic drug combinations

Abstract: Motivation: Drug combination therapy becomes promising method in the treatment of cancer. However, the number of possible drug combinations toward cancer cell lines is too large, and it is challenging to screen synergistic drug combinations through wet-lab experiments. Therefore, the computational screening has become an important way to prioritize drug combinations. Graph attention network has recently shown strong performance in screening of compound-protein interactions, but it has not been applied to the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…We observed that two deep neural networks, CCSynergy and DeepSynergy, performed better than the graph-based models, DeepDDs, TranSynergy, SAFER-C2, and SAFER-C3, achieving superior overall performance with 0.943±0.005, 0.935±0.15 of AUPRC, and 0.864±0.009, 0.845±0.013 of AUROC, which could be due to a larger number of hidden layer neurons between 2000 to 4096 that are able to capture more nuances in the data. However, such "deep" architecture is not suitable attention-based models because of graph smoothing problem (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that two deep neural networks, CCSynergy and DeepSynergy, performed better than the graph-based models, DeepDDs, TranSynergy, SAFER-C2, and SAFER-C3, achieving superior overall performance with 0.943±0.005, 0.935±0.15 of AUPRC, and 0.864±0.009, 0.845±0.013 of AUROC, which could be due to a larger number of hidden layer neurons between 2000 to 4096 that are able to capture more nuances in the data. However, such "deep" architecture is not suitable attention-based models because of graph smoothing problem (12).…”
Section: Resultsmentioning
confidence: 99%
“…DeepDDs (12) employed graph attention networks to emphasize the sub-structures of drugs' molecular graphs. While network biology helps to understand the dependence of genes and their roles in biological systems, genetic signatures may not truly reflect drug response phenotype without considering their cellular contexts.…”
Section: Introductionmentioning
confidence: 99%